2008
DOI: 10.1038/ijir.2008.3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an internet-based psychological intervention for the treatment of erectile dysfunction

Abstract: Recent research on the treatment of erectile dysfunction (ED) has focused on medical interventions, in particular oral medications. The current study examined the effectiveness of an internet-based psychological intervention for this condition. In total, 31 men (12 in treatment group, 19 in control group) completed the program. The results demonstrated that men who completed the program reported improved erectile functioning and sexual relationship satisfaction and quality. The implications of these findings f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 23 publications
1
40
1
1
Order By: Relevance
“…As well as offering convenience and privacy, online therapies can simultaneously draw together a community of clients while maintaining their anonymity (Jones & McCabe, 2011;Leusink & Aarts, 2006;Tate & Zabinski, 2004). Research into the use of Internet-based interventions for sexual dysfunctions is quite limited, but preliminary evidence from studies investigating online CBT treatments for male sexual dysfunction (MSD) suggest that Internet-based treatment may be a suitable alternative to face-to-face sex therapy (Leusink & Aarts, 2006;McCabe, Price, Piterman, & Lording, 2008;van Diest, van Lankveld, Leusink, Slob, & Gijs, 2007;van Lankveld, Leusink, van Diest, Gijs, & Slob, 2009). Data from the study by Leusink and Aarts (2006) demonstrated that 81% of participants had improved erectile function scores at the completion of therapy.…”
Section: Incorporating Mindfulness and Chat Groups Into An Online Cogmentioning
confidence: 99%
“…As well as offering convenience and privacy, online therapies can simultaneously draw together a community of clients while maintaining their anonymity (Jones & McCabe, 2011;Leusink & Aarts, 2006;Tate & Zabinski, 2004). Research into the use of Internet-based interventions for sexual dysfunctions is quite limited, but preliminary evidence from studies investigating online CBT treatments for male sexual dysfunction (MSD) suggest that Internet-based treatment may be a suitable alternative to face-to-face sex therapy (Leusink & Aarts, 2006;McCabe, Price, Piterman, & Lording, 2008;van Diest, van Lankveld, Leusink, Slob, & Gijs, 2007;van Lankveld, Leusink, van Diest, Gijs, & Slob, 2009). Data from the study by Leusink and Aarts (2006) demonstrated that 81% of participants had improved erectile function scores at the completion of therapy.…”
Section: Incorporating Mindfulness and Chat Groups Into An Online Cogmentioning
confidence: 99%
“…In a more recent study, McCabe et al. [25] reported the effectiveness of an Internet‐based CBT program for men experiencing ED. The program consisted of three main treatment components: sensate focus, communication exercises, and e‐mail contact with a therapist.…”
Section: Introductionmentioning
confidence: 99%
“…ED treatment guidelines recommend psychosexual counseling and patient education for patients with ED, but patients do not widely use such services, even when they are available [24, 25]. However, even brief psychosocial interventions can improve satisfaction with ED treatment and erectile functioning [26, 27]. Thus, PCa survivors should be offered psychosocial interventions appropriate to their literacy level to help improve their HRQOL.…”
Section: Discussionmentioning
confidence: 99%